The Pain Characteristics and Caregiver Burden in Patients With Cancer-related Pain and their Associated Factors: A Cross-sectional Study - Şefika Tuğba Yangöz; Medet Korkmaz (Journal of Holistic Nursing and Midwifery)
Introduction: Pain is the most common symptom among patients with cancer; the pain also affects their caregivers. Objective: This study aimed to explore the pain characteristics and caregiver burden in patients with cancer-related pain and their associated factors. Materials and Methods: This cross-sectional study was conducted on 240 patients and their caregivers (120 patients and 120 caregivers), who were chosen using the convenience sampling method. They completed face-to-face surveys, including information about sociodemographic and disease characteristics, the brief pain inventory, the pain beliefs questionnaire, and the Zarit burden interview scale. The descriptive statistics, frequency distributions, and multiple linear regression model were used to analyze the obtained data according to the two-tailed P<0.05. Results: The mean age of the patients was 58.79±13.46 years, and 50.8% were females. The mean age of the caregivers was 47.84±13.24 years, and 83.3% were females. The linear regression analyses showed demographic and clinical factors of patients were associated with pain severity (R2=0.326, P<0.001). In addition, these factors were associated with all sub-dimension of pain interference and pain beliefs (P<0.001). Furthermore, the linear regression model showed that patients' pain severity, pain interference and pain beliefs were predictive factors of caregiver burden (R2=0.266, P<0.001). Conclusion: These results will help health professionals understand the pain characteristics of patients and caregiver burden to improve cancer-related pain and caregiver burden.